Bacteria Cellulose and Resin Stabilization in Densified Veneer - Nugroho, Ananto; Triastuti, Triastuti; Akbar, Fazhar; Sufiandi, Sandi; Syahrial, Anne Zuflia (Trends in Sciences, 2022)
Cellulose produced by fermentation of acetic acid bacteria has high tensile strength. Meanwhile, cellulose derived from wood, which is abundant in nature, has a limit in strength. In this work, delignified wood veneer was immersed in Acetobacter xylinum culture medium to self-assemble bacterial cellulose into wood pores. Then the process was continued with a heating press. It makes the material denser and causes hydrogen bonds to form between the cellulose fibers. This study observed the densified hybrid veneer for the period of bacterial fermentation and impregnation of resin stabilization in tensile strength and dynamic mechanical analysis (DMA). The densified hybrid veneer of bacterial cellulose with resin impregnation had the maximum tensile strength after 7 days of fermentation. The DMA test showed that a densified hybrid veneer of bacterial cellulose stabilized with resin has a good ability to store cyclic energy and a damping factor that increases with temperature. HIGHLIGHTS A heating press compacted densified wood veneer with bacterial cellulose (BC), forming in hybrid veneers Hybrid veneer improves the mechanical strength Densified veneer-BC-stabilized by fermentation for 7 days had the maximum tensile strength The densified veneer that is reinforced with BC and stabilized with resin has a good ability to store cyclic energy GRAPHICAL ABSTRACT